A Kinetic Model of Whole-Body Glucose Metabolism with Reference to the Domestic Dog (Canis lupus familiaris). (8th June 2015) - McKnight, Leslie L.; Shoveller, Anna K.; Lopez, Secundino; France, James
Abstract : A new two-pool model to describe glucose kinetics in the steady state is presented. The pools are plasma glucose, Q 1, and tissue glucose, Q 2 (both µ mol). The flows (all µ mol/min) into the plasma pool (Pool 1) are absorbed glucose entry from dietary sources, labelled glucose infusion, and hepatic glucose production. There is one flow out of Pool 1, glucose uptake by the tissues. Inflows to the tissues pool (Pool 2) are from plasma and glycogenolysis. Outflows from Pool 2 are to plasma, glucose oxidation, and glycogenesis and other metabolism. Application of the model was illustrated using experimental data derived from healthy adult Labrador Retrievers in the fasted and fed (repeated meal feeding) states. In general, model derived estimates of glucose kinetics were representative of normal glucose metabolism, where rates of glucose production and uptake are similar and act to maintain blood glucose concentrations. Furthermore, estimates of within tissue glucose cycling indicated glycogenolysis in fasting and glycogenesis when fed. In the fasted state, model outputs were consistent with those reported in the canine literature derived using a single pool model.